K-pop, Aspirasi Kemodenan dan Ketidakpatuhan Strategik dalam Kalangan Wanita Melayu (K-pop, Aspiration of Modernization and Strategical Non-compliance Among The Malay Women's Circle) - Md Syed, Md Azalanshah (Universiti Kebangsaan Malaysia Press, 2019)
The popularity of K-pop among Malay women has been criticised by various parties because of its tendency to erode culture of the Malay community and violate Islamic values – two important elements in the Malaysian modernity project. For example, the participation of Malay women lamenting the death of popular K-pop artist Kim Jong-Hyun and the Korean artist group's controversial act-B1A4; embracing three tudung-clad Malay girls in Kuala Lumpur received criticism from the public and Islamic authorities. This situation has given rise to a polemic of K-pop that is considered contrary to the idea of modernity of Malaysia. Hence, this article argues that Malay women use K-pop as a platform to adapt and negotiate the aspirations of global modernity through the practice of strategic disobedience with a diverse view under personal capacity and as a member of the local fan groups. For example, this incident has earned the attention of the Department of Islamic Development Malaysia (JAKIM) and the Federal Territory Religious Department (JAWI), which consider that kind of behaviour as against the Islamic law and Malay values. This qualitative study uses thematic textual analysis approach and focuses on the diverse views and audience interpretations of K-pop in the form of comments that appear in social media such as Twitter and YouTube as well as two popular news portals – The Star and Free Malaysia Today (FMT). The findings will be analysed through two important themes – self-regulation and selected openness – and these will establish strategic disobedience as a concept to explain the popularity of K-pop and its consumption among young Malay women. © 2019, Universiti Kebangsaan Malaysia Press. All rights reserved.